Synthesis and Crystal Structure of N-[3,5-Bis(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)phenyl]-N-ethylnitrous amide and N-[3,5-Bis(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)phenyl]-N-isopropylnitrous amide - Chen, Jinsen; Chen, Pei; Yao, Huaxin; Zhu, Jin (Asian Journal of Chemistry, 2015)
The title compound N-[3,5-bis(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)phenyl]-N-ethylnitrous amide (2, m.f. C20H32N2O5B2) and N-[3,5-bis(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl]phenyl)-N-isopropylnitrous amide (4, m.f. C21H34N2O5B2) have been synthesized and characterized by elemental analysis, MS, IR, 1H, 13C, 11B NMR spectroscopies. In addition, their crystal structures were determined by single-crystal X-ray diffraction. The crystal of 2 belongs to monoclinic, space group P21/n with a = 6.3220(13), b = 28.910(6), c = 12.827(3) Å, b = 102.61(3)°, Z = 4, V = 2287.8(8) Å3, Dc = 1.167 g/cm3, μ(MoKa) = 0.081 mm-1, F(000) = 864, the final R = 0.0737 and wR = 0.1548 for 4209 observed reflections with I > 2s(I), while the compound 4 crystallizes in triclinic, space group P`1 with a = 6.8730(14), b = 10.827(2), c = 17.000(3) Å, a = 101.30(3), b = 92.07(3), g = 92.11(3)°, Z = 2, V = 1238.5(4) Å3, Dc = 1.116 g/cm3, μ(MoKa) = 0.077 mm-1, F(000) = 448, the final R = 0.0934 and wR = 0.1628 for 4546 observed reflections with I > 2s(I).